Development Of The Criminal Justice System: Initiating LPSK As A Criminal Justice Subsystem In Indonesia - I Putu Angga Feriyana; Anis Mashdurohatun; Arpangi Arpangi (Jurnal Daulat Hukum, 2020)
The development of the Criminal Justice System has led to efforts to initiate LPSK as a Criminal Justice Subsystem. The aim is to provide maximum protection to witnesses and victims of crime. The research method used is normative juridical with statutory approach, and descriptive analytical specifications. The results of the study concluded that the victimology study was a challenge for the Criminal Justice System, which had so far not paid attention to the interests of victims. Efforts to initiate LPSK as an Integrated Criminal Justice Subsystem in Indonesia are based on the importance of the institution's position in providing protection and services to victims of crime, so there is good coordination and cooperation between LPSK and other law enforcement institutions.Keywords: Development; Criminal Justice System; Initiating; LPSK.